A Conceptual Model of Intellectual Capital and Earnings Quality: The Moderating Effect of Political Connection - Alorayni, Osamah Jamal; Ganesan, Yuvaraj; Fathyah Hashim (International Journal of Psychosocial Rehabilitation, 2020)
Earnings quality reflects the integrity and quality of financial reporting which minimizes the information asymmetry and agency conflicts among management, owners, majority and minority shareholders. The issue of earnings quality has become a concern, especially in respect of intellectual capital as an intangible asset where it’s the most controversial accounting subjects in the modern era.As such, the present model sheds some light on the salience of significant role of intellectual capitals ingredients (human capital, structural capital, relational capital) in improving the level of earnings quality. The study also proposes that political connections as a moderating variable, which affect the relationship between intellectual capital and earnings quality. Political connections have often been considered as an independent variable that affects the level of earning quality in prior research. In this study, the role of political connections as a moderator variable is to extend its role from an independent variable in prior research.Finally, this study is expected to serve as a guide for the regulatory bodies such as global stock exchanges, financial institutions management as well as academic researchers.